The project No one is left behind: teaching educational research - Alessandra La Marca; Leonarda Longo (Firenze University Press, 2022)
School closures due to COVID-19 have brought significant disruptions to education. Service-learning interventions have offered significant opportunities to reduce and reverse the long-term negative effects and to empower the recovery process of pupils in difficulty. The study was carried out with 869 students enrolled in the Primary Education Sciences master's degree course at the University of Palermo. The participants have been involved in the planning and implementation of targeted educational courses designed for the "fragile" pupils from 33 different schools in Palermo. The primary level pupils were provided with a total of 60,000 hours of recovery and learning enhancement activities in remote mode. Challenging teaching activities fostered cognitive and learning development of the pupils and responsibility in teaching educational research.   Il progetto Nessuno resta indietro: formazione alla ricerca didattica. La chiusura delle scuole che ha provocato un incremento significativo della povertà educativa ha sollecitato l'opportunità di progettare interventi integrati di service learning per favorire il recupero e il potenziamento dei minori in difficoltà. 869 studenti del Corso di Laurea Magistrale in Scienze della Formazione Primaria dell'Università degli Studi di Palermo, sono stati coinvolti nella progettazione e nella realizzazione di percorsi didattici mirati, rivolti agli alunni "fragili" di 33 scuole palermitane. Complessivamente sono state erogate 60,000 ore in DAD di attività di recupero e di potenziamento dell'apprendimento di alunni della scuola primaria di Palermo. Le attività didattiche sfidanti hanno favorito la stimolazione cognitiva e lo sviluppo della motivazione per l'apprendimento degli alunni e la responsabilità nella formazione alla ricerca didattica.